KESIAPAN PEGAWAI DALAM MENGHADAPI MODERNISASI - Ali Rokhman (Jurnal Manajemen Kepegawaian, 2007)
In line with increasing target of tax revenue for each year, since 2002 Directorate General of Tax (DGT) performed tax office modernization where until the end of 2008 all of tax office will be the modern office. In support of preparing of human resource toward modernization agenda, the DGT arranged a lot of trainings that covered in many areas around Indonesia. This study analyzed effectives of the training. Type of this study is experimental study through several groups performing called workplace learning groups (WLGs). Training in Mataram in May 2007 and Sorong in August 2007 was taken as research target. Result of the study showed training in those areas run effectively and and changed knowledge and attitude of the training participants. The WLGs performing have significant impact to participant’s attitudes toward the modernization. The DGT should pay attention concerning effect of modernization and should take good practices from discussion activities in the WLGs. Keyword: human resource, organization change, modernization, workplace learning.